Adipokines and their Clinical Significance in Non-Alcoholic Fatty Liver Disease and Metabolic Disorders - Al-Nuaimi, Zaid Jaafar Awad; Mohsin, Dhuha Sabah; Mahmood, Rana Fattah; Mohsein, Osama A. (American Journal of Biology and Natural Sciences, 2025)
Adipokines are bioactive proteins secreted mainly by adipose tissue, regulating energy balance, insulin sensitivity, and inflammatory responses. Their dysregulation is strongly linked to non-alcoholic fatty liver disease (NAFLD) and associated metabolic disorders, including obesity, dyslipidemia, and type 2 diabetes mellitus. NAFLD ranges from simple steatosis to non-alcoholic steatohepatitis (NASH), and adipokines are now recognized as key mediators in this progression. Among these molecules, leptin contributes to hepatic fibrogenesis and immune activation, while adiponectin exerts protective effects by improving fatty acid oxidation, enhancing insulin sensitivity, and reducing hepatic inflammation. Conversely, pro-inflammatory adipokines such as resistin, visfatin, and chemerin worsen insulin resistance, oxidative stress, and liver injury. This imbalance between beneficial and harmful adipokines underpins the metabolic and hepatic dysfunction observed in NAFLD. Clinically, altered adipokine profiles may serve as valuable non-invasive biomarkers for early diagnosis, disease staging, and monitoring of NAFLD and metabolic disorders. Their measurement could complement existing diagnostic tools and reduce reliance on invasive procedures such as liver biopsy. Furthermore, targeting adipokine pathways through weight reduction, pharmacological interventions, and novel therapeutic strategies offers potential to improve outcomes and slow disease progression.